2020
DOI: 10.3390/mi11040434
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed MEMS Technology—Recent Developments and Applications

Abstract: Microelectromechanical systems (MEMS) are of high interest for recent electronic applications. Their applications range from medicine to measurement technology, from microfluidics to the Internet of Things (IoT). In many cases, MEMS elements serve as sensors or actuators, e.g., in recent mobile phones, but also in future autonomously driving cars. Most MEMS elements are based on silicon, which is not deformed plastically under a load, as opposed to metals. While highly sophisticated solutions were already foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 80 publications
0
31
0
1
Order By: Relevance
“…The analysis of surface tension and contact angle is carried out to present the degree of hydrophilicity before and after the plasma cleaning process, which ultimately helped us decide hydrophilicity or hydrophobicity and the wettability of the printable PVA solution. The literature found that the surface tension in the range of (25–75) mN/m is adequate to achieve a good liquid tension toward the surface [ 40 ]. Through experimentation the surface tension is found to be between 30 mN/m to 50 mN/m for both the substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of surface tension and contact angle is carried out to present the degree of hydrophilicity before and after the plasma cleaning process, which ultimately helped us decide hydrophilicity or hydrophobicity and the wettability of the printable PVA solution. The literature found that the surface tension in the range of (25–75) mN/m is adequate to achieve a good liquid tension toward the surface [ 40 ]. Through experimentation the surface tension is found to be between 30 mN/m to 50 mN/m for both the substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the MEMS fabrication process is less standardized than other microelectronics fabrication processes. 3D printed MEMS is a potential candidate among researchers for a selection of less expensive materials and producing new structures for future applications [ 40 ]. However, it may be difficult to achieve sufficient resolution only with this technology compared to traditional MEMS fabrication technology [ 36 , 37 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…MEMS (microelectromechanical systems) is a potential application of 3D printing technology using metal-based materials [ 37 , 38 , 39 ]. In this application, models produced with 3D printing technologies, from both metal-based materials and plastics, must be characterized by appropriate surface quality and dimensional accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of the surface layer obtained by additive technologies are largely influenced by technological parameters (e.g., grain size, layer thickness, printing direction, temperature, laser power, laser speed, cooling time) and the resolution of selected machines/3D printers. In the paper [ 37 ], the authors presented the possibilities of using 3D printing technology and selected machines for building MEMS models. The article mainly analyzes materials based on plastics and describes the disadvantages and advantages of currently used machines/printers in the context of the use of 3D printing to build MEMS models.…”
Section: Introductionmentioning
confidence: 99%
“…While 3D printing was originally mostly used for rapid prototyping, nowadays these techniques are more and more often used for preparing real objects with real applications. While some of these applications, such as 3D printing of microfluidics of microelectromechanical systems (MEMS), mostly strive for high resolution and accuracy [1], other applications necessitate especially good mechanical properties [2][3][4].…”
Section: Introductionmentioning
confidence: 99%